Etching time effect on photoluminescence, porosity, surface morphology and conductivity of porous silicon - Chan Kok Sheng, Wan Mohamed Zin Wan M. Khairul, Tham, Dwight, Jern Ee, Mohamad Isa Mohd Ikmar Nizam, Hassan Mohd Faiz (Universiti Pendidikan Sultan Idris, 2016)
Etching time effect on photoluminescence, porosity, surface morphology and conductivity of porous silicon by Chan Kok Sheng, Wan Mohamed Zin Wan M. Khairul, Tham, Dwight, Jern Ee, Mohamad Isa Mohd Ikmar Nizam, Hassan Mohd Faiz,